Maintaining responsible drinking: identity negotiations and emotions - Gallage, H.P. Samanthika (2018)
This thesis explores the emotions and identity negotiations of former excessive drinkers in the UK when maintaining responsible drinking. Despite the success of social marketing initiatives in promoting the adoption of healthy behaviours, sustaining them has become a major challenge. Paradoxically, this has received limited attention and discourse among social marketers. Thus, drawing insights from theories of social identity (Tajfel and Turner, 1986) and self-identity (Stryker, 1968), this study explores the nature of the emotions and identity negotiations experienced by consumers when maintaining a responsible drinking behaviour and the reasons for them to emerge. Further, the study explains how these emotions and identity negotiations affect the process of sustaining responsible drinking behaviour. Taking the view that reality is socially constructed and subjective, we explored the context specific meanings constructed by consumers using a qualitative narrative methodology. Twenty five narratives were collected using long in-depth interviews and an eight week diary, from self-reported formerly excessive drinkers in the age group of 18-35. Common themes were determined through an iterative process of analysis. In this study, we suggest that neither changing consumption behaviour nor sustaining this change is simple, straightforward or a singular act. Rather, they involve complex and emotional transformations of young adults’ lives and their social groups, rituals, possessions and activities. Due to the identity ambiguities, participants experienced emotions that are ambivalent and complex. Therefore, during the process of giving up excessive drinking, individuals were trying to reconcile and reconstruct new identities through various identity negotiations that move beyond disposing of material possessions. While some of these identity ambiguities and emotional challenges hindered the decision of maintaining a responsible drinking behaviour some of the identity negotiations resulted in positive emotions and supported sustaining the behavioural change. Theoretically, this thesis contributes to the social marketing literature by extending the understanding of changing behaviour and exploring the notion of sustaining a behavioural change in light of emotions and identity negotiations. The study also sheds light on the intertwined nature of emotions and identities and suggests the ambivalent nature of emotions by challenging the simple dichotomy (positive and negative emotions) identity theorists use to explain emotions. Further, we also argue that identity disengagement and reconstruction is a complex, holistic and a processual notion that moves beyond material possessions and encompasses consumption lifestyles, people and rituals. The study methodologically contributes to consumer research by highlighting the benefits of using diaries as a method of capturing subtle nuances in consumer behaviour. Practically, this study’s findings provide recommendations to social marketers, policy makers, charities and practitioners who are dealing with alcohol related problems, and universities, families, young adults and others seeking to manage excessive drinking. We suggest the importance of promoting alternative positive identities in social marketing messages to young people when encouraging responsible drinking rather than focusing on the negative aspects of drinking. Further, this paper proposes different strategies to normalise responsible drinking and abstinence in UK society. These recommendations highlight the importance of taking a holistic approach to encourage and maintain responsible drinking, which should focus on modifying/maintaining individuals’ selves and supporting their transformation, rather than simply their behaviour.